UV-C in Washing Treatment for Preserving Quality and Functional Content of Minimally Processed Fragaria Vesca Strawberry (Global Journal of Science Frontier Research, 2015)
The effect of UV-C radiation as sanitizer in washing treatment on the quality of minimally processed Fragaria vesca strawberry is presented. Processed strawberries were packaged in thermally sealed polypropylene trays using passive modified atmosphere packaging. During a storage period of 10 days at 4 ºC, quality parameters, functional content, sensory attributes and microbial counts analysis were performed. It was concluded that the use of UV-C radiation in the washing water was effective in reducing the microbial counts, maintaining the antioxidant compounds and the sensorial quality of the product throughout the storage period.
Keywords: industrial practices; uv-c radiation; quality attributes; functional content